A randomized controlled trial of high-intensity interval training and inspiratory muscle training for chronic heart failure patients with inspiratory muscle weakness. (March 2022) - Sadek, Zahra; Salami, Ali; Youness, Mahmoud; Awada, Charifa; Hamade, Malek; Joumaa, Wissam H; Ramadan, Wiam; Ahmaidi, Said
Objectives: Chronic heart failure is a major public health problem in which supervised exercise programs are recommended as part of non-pharmacological management. There are various reports of the success of high-intensity aerobic interval training (HI-AIT) and inspiratory muscle training (IMT) in the management of chronic heart failure patients. This study tested the hypothesis that the combination of HI-AIT and IMT could result in additional benefits over the IMT and the HI-AIT alone in terms of inspiratory muscle function, exercise capacity, and quality of life in patients with chronic heart failure and inspiratory muscle weakness. Methods: Forty patients with ejection fraction ≤45% and inspiratory muscle weakness described by maximal inspiratory pressure <70% predicted, underwent three exercise training sessions per week for 12 weeks. Patients were randomly allocated to one of four groups: the HI-AIT group, the IMT group, the combined (HI-AIT & IMT) group, and the control group. Before and after completing their training period, all patients underwent different tests that are mentioned above. Results: No changes were detected in the control group. However, the combined group, when compared to HI-AIT and IMT groups, respectively, resulted in additional significant improvement in maximal inspiratory training (62%, 24%, 25%), exercise time (62%, 29%, 12%), the 6-minute walk test (23%, 15%, 18%), and the Minnesota Living with Heart Failure Questionnaire (56%, 47%, 36%). Conclusion: In patients with chronic heart failure and inspiratory muscle weakness, the combination of the HI-AIT and the IMT resulted in additional benefits in respiratory muscle function, exercise performance, and quality of life compared to that of HI-AIT or IMT alone. Trial Registration number : NCT03538249